Analysis of a Standardized Suicide Intervention Training for Counselor Trainees - Laura Shannonhouse; Amanda D Rumsey; Nikki Elston; Mary Chase Mize; Jennifer Hightower; Yung-Wei Lin (Teaching and Supervision in Counseling, 2019)
The present study evaluates the impact of an evidence-based suicide intervention model and how pedagogical practices of counselor education programs may prepare counselors-in-training (CIT) to respond to clients who are considering suicide. Using content analysis to explore pre and post-training data, the researchers examined the impact of the 14-hour evidence-based Applied Suicide Intervention Skills Training (ASIST) on 54 CITs (76% female, 24% male; 58% White, 20% African American, 11% Latinx/Hispanic, 11% Other), with a mean age of 30 years (SD =8.6). Further data were collected 6 months later, after CITs had the opportunity to utilize suicide intervention skills during their clinical experiences. Content analysis yielded several changes between pre- and post-training data which elucidate the process of suicide intervention skill acquisition. CITs also reported having frequently applied their skills during clinical internship with clients considering suicide. Findings support the use of ASIST in the preparation of future counselors.
Keywords: Applied Suicide Intervention Skills Training; Content Analysis; Counselor Preparation